2018
DOI: 10.1007/s12603-018-1041-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Handgrip Strength Among U.S. Adults Aged 60 Years and Older from NHANES 2011–2014

Abstract: Objectives Sarcopenia is a gradual loss of muscle mass and strength that occurs with aging. This muscle deterioration is linked to increased morbidity, disability, and other adverse outcomes. Although reduced handgrip strength can be considered a marker of sarcopenia and other aging-related decline in the elderly, there is limited research on this physical health problem in at-risk groups with common biopsychosocial conditions such as depression. Our primary objective was to ascertain level of combined handgri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 49 publications
(57 reference statements)
3
57
1
1
Order By: Relevance
“…However, mental status has often been overlooked as one of the associated factors of HGS in elderly people. Depression has ever been observed to be negatively associated with HGS 25,30 . Pasco suggested that sarcopenia with resultant decreased strength and depression possibly shared a common pathophysiological pathway 31 .…”
Section: Discussionmentioning
confidence: 99%
“…However, mental status has often been overlooked as one of the associated factors of HGS in elderly people. Depression has ever been observed to be negatively associated with HGS 25,30 . Pasco suggested that sarcopenia with resultant decreased strength and depression possibly shared a common pathophysiological pathway 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Results demonstrated significant differences in all indicators of depression after completing 12 weeks of training [35], that low muscle strength increased depression symptomatology in patients with fibromyalgia [37], and that strength training intervention significantly decreased depressive symptoms [36]. The other observational studies showed that independently of sex, age, and country, depression symptoms were significantly associated with a reduced handgrip strength [11,21,22,24,[27][28][29][30][38][39][40]. Furthermore, adults in the lower tertile or quartile for muscle strength had a significantly higher risk for depressive symptoms compared with those in the third tertile or fourth quartile [23,25,26,31].…”
Section: Principal Findingsmentioning
confidence: 94%
“…For the five clinical trial studies, the instruments used to assess the muscular strength or the depression symptoms were different among the studies. From the 16 observational studies, the data from 9 were used for meta-analysis [11,[21][22][23][24][25][26][27][28]. The seven studies not included were eliminated based on the heterogeneity of the association measure between muscular strength and depression symptoms.…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Active surveillance is a promising approach for low risk PC, yet a significant number of men still opt for more aggressive treatments such as surgery and radiation that often result in sexual, bowel and urinary dysfunction [3]. These significant ongoing health-related quality of life (HRQL) challenges may cause men to become depressed, less-active and dis-engaged from activities of daily living (ADL's) [4][5][6], which could further influence their physical HRQL. Furthermore, disease progression and treatment-related factors can exacerbate already compromised functioning.…”
Section: Introductionmentioning
confidence: 99%